Artificial Sun Protection: Sunscreens and Their Carrier Systems - Villalobos-Hernandez, J. R.; Muller-Goymann, C. C. (Current Drug Delivery, 2006)
The formulation of sunscreens products requires information about the properties of the substances responsible for the sun protection, their action mechanisms and the vehicles used for their administration. The improvement of the performance of sunscreen substances by a modification of their chemical, physical and technological properties or by the use of conventional and novel carriers is described in this review. The sun protection achieved by the use of sunscreens incorporated into carriers in terms of the sun protection factor (SPF) and other performance indices is also shown. Current manufacturing methods to incorporate sunscreen substances into vehicles are briefly described. Furthermore, basic information related to the dermatological effects of the UV radiation classified according to the different spectral regions of the UV radiation is presented in this manuscript.
Keywords: Artificial sun protection